1968
DOI: 10.1080/00288233.1968.10431639
|View full text |Cite
|
Sign up to set email alerts
|

The influence of herbage height at treading and treading intensity on the yields and botanical composition of a perennial ryegrass-white clover pasture

Abstract: To cite this article: K. R. Brown (1968) The influence of herbage height at treading and treading intensity on the yields and botanical composition of a perennial ryegrass-white clover pasture, New Zealand Journal of Agricultural Research, 11:1, 131-137, DOI: 10.1080/00288233.1968 ABSTRACTThe effects of sheep treading and herbage cover at treading on the yield and botanical composition of a perennial ryegrass-white clover pasture were assessed at four rates of treading.Where pasture was trodden before the he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

1977
1977
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 2 publications
2
19
0
Order By: Relevance
“…These interactions offered no evidence of protection against treading damage from a higher stubble as found by Brown (1968). The first interaction revealed paspalum leaf yield to be depressed more severely by treading (TI5 and T60) in the 5 ern stubble treatment, and the second showed increased yield per tiller with a 5 ern stubble only in the absence of treading (TO).…”
Section: Treading Effectsmentioning
confidence: 91%
See 1 more Smart Citation
“…These interactions offered no evidence of protection against treading damage from a higher stubble as found by Brown (1968). The first interaction revealed paspalum leaf yield to be depressed more severely by treading (TI5 and T60) in the 5 ern stubble treatment, and the second showed increased yield per tiller with a 5 ern stubble only in the absence of treading (TO).…”
Section: Treading Effectsmentioning
confidence: 91%
“…The influence of grazing on paspalum production may be associated with animal effects of biting or treading, or interspecific plant competition which mav interact with each other and with other factors 'such as height of defoliation or seasons (Brown 1968). Treading by sheep depresses the growth of all species but there is significant variation in susceptibility among species (Edmond 1966).…”
Section: Introductionmentioning
confidence: 99%
“…A reduction in annual pasture production because of animal treading has been shown in various studies and ranges from 0 to 38% (e.g., Campbell 1966;Brown 1968;Edmond 1970;Mullen et al 1978;Drewry & Paton 2000). Short-term reductions in DM yield can be even more severe, with a reduction in DM yield of up to 81% over a 5-month period following intensive treading by cattle (Cluzeau et al 1992).…”
Section: Effect Of Animal Treading and Traffic On Pasture Productionmentioning
confidence: 99%
“…Short-term reductions in DM yield can be even more severe, with a reduction in DM yield of up to 81% over a 5-month period following intensive treading by cattle (Cluzeau et al 1992). Various studies have shown the highest reductions in DM yield at higher stocking rates, or when the treading damage was not (partly) compensated for by the input of excretal nutrients (Bryant & Blaser 1961, 1968Charles & Valentine 1978;Cluzeau et al 1992). Edmond (1970) showed that annual yield increased when pasture was grazed at low stocking rates, compared with no grazing, but decreased at a very high stocking rate.…”
Section: Effect Of Animal Treading and Traffic On Pasture Productionmentioning
confidence: 99%
“…Similarly, plant growth is improved by cattle dung (Bornemissza & Williams 1970;MacDiamid & Watkin 1971) and urine (Norman & Green 1958;During & McNaught 1961). However, trampling by stock (Edmond 1974;Brown 1968) can reduce pasture production, as will overgrazing. The beneficial effects of grazing stock can be manipulated to outweigh the detrimentai effects in managed situations.…”
Section: Introductionmentioning
confidence: 99%